Impact of Bridge to Transplantation With Continuous-Flow Left Ventricular Assist Devices on Posttransplantation Mortality: A Propensity-Matched Analysis of the United Network of Organ Sharing Database. Issue 6 (6th August 2019) - Truby, Lauren K.; Farr, Maryjane A.; Garan, A. Reshad; Givens, Raymond; Restaino, Susan W.; Latif, Farhana; Takayama, Hiroo; Naka, Yoshifumi; Takeda, Koji; Topkara, Veli K.
Abstract : Background: Bridge to transplantation (BTT) with left ventricular assist devices (LVADs) is a mainstay of therapy for heart failure in patients awaiting heart transplantation (HT). Criteria for HT listing do not differ between patients medically managed and those mechanically bridged to HT. The objectives of the present study were to evaluate the impact of BTT with LVAD on posttransplantation survival, to describe differences in causes of 1-year mortality in medically and mechanically bridged patients, and to evaluate differences in risk factors for 1-year mortality between those with and those without LVAD at the time of HT. Methods: Using the United Network of Organ Sharing database, we identified 5486 adult, single-organ HT recipients transplanted between 2008 and 2015. Patients were propensity matched for likelihood of LVAD at the time of HT. Kaplan–Meier survival estimates were used to assess the impact of BTT on 1- and 5-year mortality. Logistic regression analysis was used to evaluate the odds ratio of 1-year mortality for patients BTT with LVAD compared with those with medical management across clinically significant variables at various thresholds. Results: Early mortality was higher in mechanically bridged patients: 9.5% versus 7.2% mortality at 1 year ( P <0.001). BTT patients incurred an increased risk of 1-year mortality with an estimated glomerular filtration rate of 40 to 60 mL·min −1 ·1.73 m −2 (odds ratio, 1.69; P =0.003) and <40 mL·min −1 ·1.73 m −2 (odds ratio, 2.16; P =0.005). A similar trend was seen in patients with a body mass index of 25 to 30 kg/m 2 (odds ratio, 1.88; P =0.024) and >30 kg/m 2 (odds ratio, 2.11; P <0.001). When patients were stratified by BTT status and the presence of risk factors, including age >60 years, estimated glomerular filtration rate <40 mL·min −1 ·1.73 m −2, and body mass index >30 kg/m 2, there were significant differences in 1-year mortality between medium- and high-risk medically and mechanically bridged patients, with 1-year mortality in high-risk BTT patients at 17.6% compared with 10.4% in high-risk medically managed patients. Conclusions: Bridge to HT with LVAD, although necessary because of organ scarcity and capable of improving wait list survival, confers a significantly higher risk of early posttransplantation mortality. Patients bridged with mechanical support may require more careful consideration for transplant eligibility after LVAD placement. Abstract : Supplemental Digital Content is available in the text.